Advanced materials for cancer treatment and beyond - Zhang, Lei; Wang, Yanan; Li, Yangjia; Chen, Zhe-Sheng; Hu, Chaohua (Frontiers in Pharmacology, 2025)
Conservative anti-cancer treatment represented by chemotherapy and surgery lacks tumor-specificity and could hardly resolve the problems associated with multidrug resistance (MDR) in cancers. Novel therapeutic materials in cancer treatment, such as those with anti-MDR or controllable treatment features, represent a significant trend due to their advantages of high and specific efficacy and timely intervention of cancer progress. In addition to their excellent biocompatibility and specificity, they can be utilized in therapies that require ease of operation, provided they are designed with high detection sensitivity. In this review, we summarize a series of recently developed materials that exhibit these advantages, including immune-enhancing and tumor microenvironment (TME)- responsive materials, and those with integrated therapeutic and imaging capabilities. We also introduce advanced modification approaches that can impart essential targeting functionalities to these materials.